Systematic review of randomised clinical trials on topical ciclosporin A for the treatment of dry eye disease. Issue 8 (16th December 2013) - Sacchetti, Marta; Mantelli, Flavio; Lambiase, Alessandro; Mastropasqua, Alessandra; Merlo, Daniela; Bonini, Stefano
Abstract : Aims: Topical ciclosporin A (CsA) is a therapeutic option for dry eye disease (DED) to control ocular surface inflammation and improve tear function. The aim of this study is to systematically review data from randomised clinical trials (RCTs) evaluating efficacy and safety of topical CsA treatment for DED. Methods: Articles published up to December 2012 were identified from Medline, Embase and the Cochrane Controlled Trials Register. A total of 18 RCTs that evaluated the efficacy and safety of different topical CsA formulations for the treatment of DED were selected according to the set criteria. The Jadad score was calculated to assess RCT quality. Results: The mean Jadad score of the included RCTs was 2.8±0.6. All CsA formulations proved safe for the treatment of DED. Symptoms improved in 100% (9/9) RCTs, tear function improved in 72% (13/18) RCTs and ocular surface damage was ameliorated in 53% (9/17) RCTs in patients with DED. No improvements with CsA treatment versus control were observed in DED resulting from surgical procedures, contact lens use and thyroid orbitopathy. Statistical comparison of CsA efficacy through a meta-analysis of data was not possible due to a lack of standardised criteria and comparable outcomes among studies. Conclusions: Although topical CsA appears to be a safe treatment for DED, evidence emerging from RCTs is limited, and this affects the strength of recommendations to healthcare providers and policymakers for optimal management. Standardised diagnostic criteria to assess the efficacy of topical CsA are recommended to improve the design of future RCTs in DED.